Pengaruh DER, Roa, NPM dan EPS Terhadap Underpricing Studi Kasus: Perusahaan Yang Melakukan Initial Public Offering di BEI - Meutia Octafian; Anita Wijayanti; Endang Masitoh (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
This study aims to look at the effect of each variable (DER, ROA, NPM, EPS) on underpricing in companies conducting an initial public offering on the Stock Exchange in 2016-2018. Testing is done by using a sample of 31 companies that conducted an initial public offering listed on the Indonesia Stock Exchange in 2016 -2018, using purposive sampling method. Data processing methods use SPSS with descriptive tests, classic assumption tests, and in the measurement of hypotheses using multiple regression analysis. The results in this study address the influence of ROA and EPS on underpricing, while DER and NPM have no effect on underpricing. It is expected that this research can be used as a material consideration for investors in analyzing financial statements that will be used as a reference in investing, while for academics can add knowledge related to the influence of several fundamental factors on underpricing.